KORELASI KADAR FIBRINOGEN DENGAN NILAI ALBERTA STROKE PROGRAM EARLY CT SCORE ASPECTS PADA STROKE ISKEMIK - Dian Tunjungsari, Nasirun Zulqarnaen, Dwi Pudjonarko (Neurona Majalah Kedokteran Neuro Sains, 2015)
INTRODUCTION ALBERTA STROKE PROGRAM EARLY CT SCORE ASPECTS IS A SCORING SYSTEM TO ASSESS EARLY ISCHEMIA AT THE TERRITORY OF THE MIDDLE CEREBRAL ARTERY MCA FROM NONCONTRAST BRAIN COMPUTED TOMOGRAPHY SCAN IN ISCHEMIC STROKE FIBRINOGEN LEVELS REFLECT THE MAGNITUDE OF THROMBOTIC POTENTIAL OF BLOOD AND ONE OF THE HEMATOLOGIC FACTORS THAT IS CLOSELY RELATED TO CARDIOVASCULAR DISEASE